The Politics of Learning from Rare Events - Rerup, Claus; Zbaracki, Mark J. (Organization Science, 2021)
Actors engaged in learning from rare events must trade off between two different criteria for effective learning: validity—the extent to which learning can be used for understanding, prediction, and control—and reliability—the extent to which understandings of experience are public, stable, and shared. Existing models of learning from rare events have elided conflict and politics by assuming that individuals and organizations always seek new valid knowledge that then becomes public, stable, and shared across actors. Here we examine the politics of learning in a historical analysis of population-level learning by four different actors following the 1994 sinking of the ferry Estonia. We show how politics shaped the trade-off between reliability and validity and, in turn, shaped the nature of the learning. Whereas the new knowledge was sometimes both valid and reliable, the more common outcome was knowledge that was only partly valid and reliable. Rather than treat these outcomes as substandard, we show how they are important to the dynamics of learning, as different population-level actors take into account different aspects of experience. The result is a model that makes conflict and contestation—and hence politics—essential to effective learning.